A randomized controlled trial of unguided internet cognitive behaviour therapy for perfectionism in adolescents: Impact on risk for eating disorders. (September 2019) - Shu, Chloe Y.; Watson, Hunna J.; Anderson, Rebecca A.; Wade, Tracey D.; Kane, Robert T.; Egan, Sarah J.
Abstract: Objective: Perfectionism is a risk factor for the development and maintenance of eating disorders. The objective of this study was to examine the efficacy of unguided Internet cognitive behaviour therapy for perfectionism (ICBT-P) as a treatment and prevention for perfectionism and symptoms of eating disorders, anxiety, depression and self-esteem in female adolescents. Method: Young women ( N  = 94, 14–19 years) who self-identified as having difficulties with perfectionism but did not have a clinical eating disorder diagnosis were recruited. Participants were randomly allocated into one of three groups: unguided ICBT-P, unguided ICBT for nonspecific stress management (ICBT-S), or waitlist control. Results: All analyses were intent-to-treat. ICBT-P resulted in the most favorable outcomes at post-treatment and 3- and 6-months follow-up. ICBT-P was superior to control on all outcome measures at 3- and 6-months and superior to ICBT-S on all outcomes over most time points ( d s = 0.13–0.94). Clinical significance analysis demonstrated that the treatment prevented symptom increases over 6-month follow-up, with ICBT-P superior to ICBT-S in prevention of clinical perfectionism and depressive symptoms, and ICBT-P superior to waitlist control in prevention of eating disorder symptoms. There was relatively high attrition, although there were no differences in attrition between the groups at 3- and 6-month follow-up and rates were commensurate with other Internet interventions. Discussion: The findings support unguided ICBT-P as a useful target for preventing eating disorder and associated symptoms in female youth who self-identify as perfectionistic. Anzctr trial number: ACTRN12615001098527. Highlights: Perfectionistic female adolescents with no eating disorder diagnosis participated. Participants were randomized to three conditions. Unguided Internet cognitive behaviour therapy for perfectionism (ICBT-P). Unguided Internet stress management (ICBT-S) or waitlist control. ICBT-P was superior to control on all outcome measures at 3- and 6-months.